2019
DOI: 10.4314/wiojms.v18i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale milkfish (Chanos chanos) farming in Kenya: An overview of the trends and dynamics of production

Abstract: A number of donor-funded projects by NGOs, government departments and faith-based organizations have piloted milkfish farming along the coast of Kenya at different scales with the aim of addressing poverty and food security at the community level. This paper provides an overview of the history of milkfish farming, organisation of operations, funding, farmers trends, and production dynamics, using both secondary and primary data. Primary data were obtained from quantitative and qualitative assessments c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
7
1
1
Order By: Relevance
“…The low milk sh production in the studied area is related to lack of or low education level. In this study, majority of the milk sh farmers had no formal education and only a handful completed primary education, similar to results obtained for milk sh farmers in Kenya (Mirera 2019). Education is key for small-scale farmers to acquire farming knowledge and skills in order to improve farming and enhance productivity (Haimene 2018).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The low milk sh production in the studied area is related to lack of or low education level. In this study, majority of the milk sh farmers had no formal education and only a handful completed primary education, similar to results obtained for milk sh farmers in Kenya (Mirera 2019). Education is key for small-scale farmers to acquire farming knowledge and skills in order to improve farming and enhance productivity (Haimene 2018).…”
Section: Discussionsupporting
confidence: 78%
“…The ndings from the present study indicated that milk sh farmers produced 307 kg/m 2 per production cycle equivalent to 458 kg/ha, which is lower than a production ranging from 700 to 1,500 kg/ha (Sumagaysay-Chavoso 2003), and 839 kg/ha (Sumagaysay and Borlongan 1995) reported in Philippines and 525 kg/ha recorded in Indonesia (Limi and Dewi 2023). However, the obtained yield is higher than 0.45 kg/m 2 reported for milk sh farming in Kenya (Mirera 2019). The low milk sh production in the studied area is related to lack of or low education level.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Ikan Bandeng (Chanos chanos) merupakan ikan bernilai ekonomis penting yang telah banyak dibudidayakan diberbagai negara seperti Indonesia (Sulistijowati andMile 2016), Filipina (Santander-de Leon et al 2015), Taiwan (Chiang et al 2004), India (Lalramchhani et al 2019), Srilangka (Vasava et al 2018), Kenya (Mirera, 2019), Tanzania (Mwangamilo dan Jiddawi, 2003), dan Kepulauan Solomon (Blythe et al 2017). Ikan Bandeng banyak dikonsumsi karena mempunyai nilai gizi yang tinggi (Malle et al 2019).…”
Section: Pendahuluanunclassified
“…Recently, the environmental authorities of the West-Indian Ocean have developed conservation programs focused on the restoration of mangrove ecosystems and regulation of crabs' fisheries to ensure the resource sustainability (e.g. Mirera et al 2017a). In this context, improving knowledge of crabs' ecology is essential to better understand population dynamics and, in turn, to efficiently guide restoration and preservation plans.…”
Section: Introductionmentioning
confidence: 99%